Exploring differences in competitive performance based on Miles and Snow's strategy typology for the semiconductor industry. Issue 6 (14th April 2020) - Lin, Chinho; Chiu, Yu-Wen; Chen, Wen-Chieh; Ting, Shu-Fang
Abstract : Purpose: The aim of this article is to construct a performance evaluation framework that can be employed in companies to enhance their business operations and strengthen their financial advantage in the current environment. To validate the approach, a case example has been included to assess the practicality and validity of this approach when applied in a real environment. Design/methodology/approach: This study focuses on an important part of the strategic planning process: internal scrutiny and environmental (external) scanning, in which an evaluation of company performance is divided into two stages by using network DEA and the cross-efficiency approach. In addition, this article employs Miles and Snow's typology for classifying the strategies used by companies. Findings: The analytical results show that the proposed framework can be useful for companies seeking to evaluate which strategies may be the most appropriate, based on Miles and Snow's typology, to effectively reallocate limited resources. Research limitations/implications: The evaluation in this study only uses financial data and does not take other nonfinancial indicators into consideration. Originality/value: This research provides value by classifying each company included in the study in terms of its capability and financial efficiency according to Miles and Snow's system of strategy classification. Second, an internal and external performance measuring framework is constructed. Finally, some propositions for top management are provided by analyzing the financial advantages of using a performance evaluation framework that can help top management make decisions more objectively.